941 EFFECTIVENESS OF ACUTE GERIATRIC UNIT CARE AMONG HOSPITALISED OLDER ADULTS WITH ACUTE MEDICAL COMPLAINTS: A META-ANALYSIS. (14th June 2022) - O'Shaughnessy, Í; Robinson, K; O'Connor, M; Conneely, M; Ryan, D; Steed, F; Carey, L; Leahy, A; Shanahan, E; Quinn, C; Galvin, R
Abstract: Introduction: Older adults are clinically heterogeneous and are at increased risk of adverse outcomes during hospitalisation due to the presence of multiple comorbid and complex conditions. This systematic review and meta-analysis aims to update and synthesise the totality of research evidence on the effectiveness of acute geriatric unit (AGU) care for older adults admitted to hospital with acute medical complaints. Method: MEDLINE, CINAHL, CENTRAL, and Embase databases were systematically searched from 2008 to February 2021. Screening, data extraction, and quality grading were undertaken by two reviewers. Only trials with a randomised design comparing AGU care and conventional care units were included. Meta-analyses were performed in Review Manager 5.4 and the Grading of Recommendations, Assessment, Development and Evaluations framework was used to assess the certainty of evidence for outcomes reported. The primary outcome measure was incidence of functional decline between baseline two-week prehospital admission status and discharge and at follow-up. Results: 11 trials recruiting 7, 496 participants across three countries were included. AGU care was associated with a 23% reduction in functional decline at six-month follow-up (risk ratio (RR) 0.77, 95% confidence interval (CI) 0.64–0.92; moderate certainty evidence), and significant cost savings (mean difference (MD) -538.01USD, 95% CI -571.05USD—-504.96USD; low certainty evidence). No differences were found in functional decline at hospital discharge or at three-month follow-up, length of hospital stay, the likelihood of living at home, mortality, hospital readmission, cognitive function, or patient satisfaction with the index admission. Conclusion: AGU care improves clinical and process outcomes for older adults admitted to hospital with acute medical complaints. Future research should focus on greater inclusion of clinical and patient reported outcome measures including quality of life. Use of such measures may lead to a greater focus on patient-centered care and service provision priorities.